2010
DOI: 10.2119/molmed.2009.00160
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 Activation Promotes Antithrombotic Activity

Abstract: Hyperactivity of the axis ACE/AngII/AT1R of the renin‐angiotensin system is associated with occurrence of acute thrombotic event. Recently a novel concept of a counterrugulatory axis, ACE2/Ang‐(1‐7)/Mas, has emerged. We hypothesized that ACE2 would be protective against thrombosis. Thrombus was induced in the vena cava of SHR and WKY rats by FeCl3 solution. ACE2 and ACE protein expression and activities in the thrombus were determined by Western blot and fluorogenic kinetic assays, respectively. Real time thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
134
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(139 citation statements)
references
References 28 publications
3
134
0
2
Order By: Relevance
“…Experimental data support the concept that intrarenal expression of ACE2 is altered in diabetes [12,27,28]. Furthermore, ACE2 may provide vascular and renal protection since a genetic deficiency or pharmacological inhibition of ACE2 causes increased prothrombotic, atherogenic and inflammatory activity as well as worsening of albuminuria [9,12,[29][30][31].…”
Section: Ace2 Activity Increases In T1d Patientsmentioning
confidence: 69%
See 1 more Smart Citation
“…Experimental data support the concept that intrarenal expression of ACE2 is altered in diabetes [12,27,28]. Furthermore, ACE2 may provide vascular and renal protection since a genetic deficiency or pharmacological inhibition of ACE2 causes increased prothrombotic, atherogenic and inflammatory activity as well as worsening of albuminuria [9,12,[29][30][31].…”
Section: Ace2 Activity Increases In T1d Patientsmentioning
confidence: 69%
“…Our results partly confirm the observations made in experimental diabetes, but also raise the question of whether data from rodents with experimental diabetes can be readily translated into human disease. Recent experimental data prove that overexpression of ACE2 counterbalances the harmful effects of Ang II in the vasculature [44,45], and that genetic deficiency or pharmacological inhibition of ACE2 causes increased prothrombotic, atherogenic and inflammatory activity [29,30]. Whether an alteration in ACE2 gene and/or protein expression contributes to the progression of diabetic nephropathy or vascular injury remains still an open question.…”
Section: Ace2 Activity Increases In T1d Patientsmentioning
confidence: 99%
“…Nevertheless, these findings open the door to the possibility that miR-421 may be useful as a diagnostic or prognostic indicator in cardiovascular disease. To date, understanding the biological roles of miR-421 is limited, but a recent study identified a possible role for miR-421 in thrombosis [20], a pathology also linked to ACE2 dysregulation [33]. Furthermore, Marchand et al [20] identified SERPINE-1 as a direct target of miR-421.…”
Section: -Utrmentioning
confidence: 99%
“…T-lymphocytes [52] and platelets [53] are implicated in contributing to atherosclerosis formation. Intraperitoneal administration of human recombinant ACE2 inhibits T-cell infiltration into the kidney [54] and pharmacological activation of ACE2 by XNT, a small-molecular ACE2 activator [33], inhibits platelets from attaching to ECs [55]. It is therefore possible that these two cell types might be important in the anti-atherosclerotic effects of ACE2 and future work is needed to clarify this.…”
Section: Future Directionsmentioning
confidence: 99%